RTÉ and the globalisation of Irish Television - Corcoran, Farrel John, 1946- (Intellect, 2004)
For about 40 years, RTE's radio and television channels have played an enormous role in shaping Irish social and cultural life. As the national publicly owned and funded broadcaster, RTE is the biggest cinema, school, sports stadium, market square, performance stage, town crier and concert hall in Ireland. It sets the agenda for the national conversation that drives modern Ireland. This work is a study of the structural transformations now taking place in Irish broadcasting. The book will focus on the broadcasting section generally, but primarily on RTE, as it adjusts to a number of radical ch.